Exercise Capacity in Asymptomatic Adult Patients Treated for Coarctation of the Aorta - Dijkema, Elles J. (Pediatr Cardiol, 2019)
A reduced exercise capacity is a common finding in adult congenital heart disease and is associated with cardiovascular morbidity and mortality. However, data on exercise capacity in patients after repair of coarctation of the aorta (CoA) are scarce. Furthermore, a high rate of exercise-induced hypertension has been described in CoA patients. This study sought to assess exercise capacity and blood pressure response in asymptomatic patients long-term after CoA repair in relation to left ventricular and vascular function. Twenty-two CoA patients (age 30 ± 10.6 years) with successful surgical repair (n = 12) or balloon angioplasty (n = 10) between 3 months and 16 years of age with a follow-up of > 10 years underwent cardiopulmonary exercise testing at a mean follow-up of 23.9 years. Exercise capacity (peak oxygen uptake; VO(2peak)) and blood pressure response were compared to age- and gender-matched reference values. Left ventricular function and volumetric analysis was performed using cardiovascular magnetic resonance imaging. CoA patients showed preserved exercise capacity compared to the healthy reference group, with a VO(2peak) of 41.7 ± 12.0 ml/kg/min versus 44.9 ± 6.7 ml/kg/min. VO(2peak)/kg showed a significant association with age (p < 0.001) and male gender (p ≤ 0.001). Exercise-induced hypertension occurred in 82% of CoA patients, and was strongly related to left ventricular mass (p = 0.04). Of the 41% of patients who were normotensive at rest, 78% showed exercise-induced hypertension. No significant correlation was found between peak exercise blood pressure and age, BMI, age at time of repair, LVEF, or LV dimensions. Exercise capacity is well preserved in patients long-term after successful repair of coarctation of the aorta. Nevertheless, a high number of patients develop exercise hypertension, which is strongly related to systemic hypertension. Regular follow-up, including cardiopulmonary exercise testing, and aggressive treatment of hypertension after CoA repair is strongly advised.